Facebook and Yoga Gurus, New Age, and Spirituality through Social Media. - Pandya, S. P.
This article reports a three-year repeated measures study on the effect of guru-led new religious movements? (gnrm) customized Facebook yoga lessons on followers? spiritual experiences and religious commitment. Participants comprised 3,488 followers across four gnrms. During the study period, each gnrm Facebook page had an average of 1,095 daily posts and 156 weekly yoga lessons. Results showed that at phase 2, scores of participants on spiritual experiences and religious commitment measures were significantly higher vis-à-vis the comparison group. Within the participant cohort, women, those with stable marital status, and those who performed a combination of devotional and social service activities at the gnrms scored higher. Disciplined Facebook usage influenced regular viewing of the customized yoga lessons, higher quiz scores, and regular self-practice. The strongest predictor of the phase 2 outcome measure scores was regular self-practice. With focused administering and usage, Facebook is an effective medium for intensifying spiritual experiences and religious commitment among gnrms? fellowship.